Buddhism of Japanese Immigrants within the framework of Brazilian Buddhism - Frank Usarski (Horizonte, 2016)
The article reflects upon Buddhism of Japanese immigrants, which is the historically and numerically most important sub-segment of the so-called “ethnic Buddhism” in Brazil. The latter represents - in distinction from the “Buddhism of converts” - one of the two principles analytical subcategories of Buddhist universe of the country. The text starts with a reconstruction of the trajectory of the religious sub-segment in question by relating it to other observable tendencies in Brazil’s Buddhist field in general. For analytical reasons, the history of Buddhism of Japanese immigrants is subdivided into four phases. In the second part of the article the aforementioned data are interpreted from a sociological point of view. This interpretation refers mainly to the statistics of the National Census from 1950 onwards conducted by the Brazilian Institute of Geography and Statistics (IBGE). The data indicate a gradual decline of Japanese Immigrant Buddhism during the last decades that has cumulated into general crises of the Buddhist segment in question. As for factors possibly responsible for this negative development, the article discusses aspects such as logistical failures on the side of the Buddhist institutions or the difficulties of the families of Japanese descendants in handing down their cultural and religious heritage to their children.